Perancangan Aplikasi Registrasi Pasien Rawat Jalan Menggunakan Barcode Di Rumah Sakit Umum Daerah Ajibarang - Anggita, Anggita Tri Setia Ningrum; Ilham Rahmansyah; Khusnul Khotimah Arum N (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Patient registration services are the first step in the entire hospital service chain. The manual registration process that is still widely used causes long queses, long waiting times, and reduces patient satisfaction. To overcome this, the Ajibarang Regional General Hospital (RSUD) has developed an innovative barcode based service called SIAP CERIA (Fast, Responsive, Informative, and Accountable Service Application Information System). This study aims to design a simpler, more interactive barcode based outpatient patient registration application user interface that meets the needs of both patients and staff. The method used is the Waterfall model of the System Development Life Cycle (SDLC) approach, through the stages of needs analysis, design, and prototype creation using Figma. The results of this research are the design of an outpatient registration application interface that includes a login page, new patient registration, general and BPJS patient registration, schedule and doctor selection, medical resume, and a barcode feature to speed up the patient check-in process. This interface design is expected to improve the efficiency of registration services, reduce queues, and provide a better user experience.